2021
DOI: 10.1186/s42506-021-00075-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, life style, and occupational factors associated with lower limb varicose veins: a case control study

Abstract: Background Few data were documented about risk factors for lower limb varicose veins (LLVV) among Egyptian population. Identifying modifiable risk factors is crucial to plan for prevention. The current research aims to study the epidemiological, life style, and occupational factors associated with LLVV in a sample of Egyptian population. Methods A case control study was adopted. Cases with LLVV (n = 150) were compared with controls (n = 150). Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
4
4
0
1
Order By: Relevance
“…There is no consistency in the literature whether smoking plays an important role in the development of varicose veins. In line with the present study, some authors did not observed such relationship; 23 , 24 conversely, Yuan et al recently reported that smoking is an independent risk factor (OR = 2.53; 95%CI = 1.15–5.58), 25 whereas other authors found that there may be a positive association between genetic predisposition to smoking initiation and risk for varicose veins (OR = 1.12; 95%CI = 1.04–1.22; p = 0.004). 26 Based on Burkit's hypothesis on the association between intestinal transit time and different diseases, constipation emerges as a factor that some authors relate to the development of varicose veins, due to increased intra-abdominal pressure; 27 however, the association with this factor could not be confirmed, since prevalence in this population was low.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There is no consistency in the literature whether smoking plays an important role in the development of varicose veins. In line with the present study, some authors did not observed such relationship; 23 , 24 conversely, Yuan et al recently reported that smoking is an independent risk factor (OR = 2.53; 95%CI = 1.15–5.58), 25 whereas other authors found that there may be a positive association between genetic predisposition to smoking initiation and risk for varicose veins (OR = 1.12; 95%CI = 1.04–1.22; p = 0.004). 26 Based on Burkit's hypothesis on the association between intestinal transit time and different diseases, constipation emerges as a factor that some authors relate to the development of varicose veins, due to increased intra-abdominal pressure; 27 however, the association with this factor could not be confirmed, since prevalence in this population was low.…”
Section: Discussionsupporting
confidence: 90%
“…No hay consistencia en la literatura acerca de si el tabaquismo juega o no un papel importante en el desarrollo de várices. Al igual que en este estudio, algunos no encuentran esta relación 23 , 24 ; sin embargo, recientemente, Yuan et al reportan que el cigarrillo es un factor de riesgo independiente (OR = 2.53; IC95% = 1.15, 5.58) 25 , mientras que otros encuentran que pudiera haber una asociación positiva en la predisposición genética a fumar con el riesgo de várices (OR = 1,12; IC95% = 1,04–1,22; p = 0,004) 26 . Desde la hipótesis de Burkit sobre el tránsito intestinal lento y su asociación con diferentes enfermedades, la constipación aparece como un factor relacionado por algunos autores para el desarrollo de várices por el aumento de la presión intrabdominal 27 .…”
Section: Discussionunclassified
“…(Z=0.58; P=0.56). No significant association was found between smoking and alcoholism and the occurrence of varicose veins which was comparable with the reports of Carpentier et al [25] but contrary to the findings of Gourgou S et al [21] Elamrawy et al [26] noted that smoking was an independent predictor of lower limb varicose veins, smokers had a 2.53 times greater risk to develop varicose veins. They even noted that smoking intensity was significantly associated with varicose veins; moderate/heavy smokers had a 6.27 times greater risk to develop varicose veins.…”
Section: Discussionsupporting
confidence: 83%
“…The frequency of CVI is quite controversial, according to several studies in which different data is presented. Thus, it may be said that it is present in 5-25% of the population depending on which part of the world is concerned [4][5][6].…”
Section: Introductionmentioning
confidence: 99%